2010
DOI: 10.5012/bkcs.2010.31.8.2261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Graphenes/CNTs Co-reinforcement on Electrical and Mechanical Properties of HDPE Matrix Nanocomposites

Abstract: In this work, mechanical and electrical properties of graphenes (GP)/carbon nanotubes (CNTs) co-reinforced high density polyethylene (HDPE) matrix composites were studied. The microstructure, morphologies, and electric properties of the composites were evaluated by XRD, TEM, and 4-probe methods, respectively. It was found that the electric resistivity of 0.5 wt %-GP/HDPE was immeasurable, and 2.0 wt %-CNTs/HDPE showed high resistivity (6.02 × 10 4 Ω·cm). Meanwhile, GP (0.5 wt %)/CNTs (2.0 wt %)/HDPE showed exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A previous report [ 30 ] confirmed that when carbon nanotubes and graphite platelets were mixed, electromagnetic interference shielding properties significantly improved at a specific ratio of the two fillers. That is, when mixing different types of fillers with different shapes, the dispersion degree of the fillers can be significantly enhanced at a golden mixing ratio so that a pathway for electric conduction is effectively formed.…”
Section: Resultsmentioning
confidence: 62%
“…A previous report [ 30 ] confirmed that when carbon nanotubes and graphite platelets were mixed, electromagnetic interference shielding properties significantly improved at a specific ratio of the two fillers. That is, when mixing different types of fillers with different shapes, the dispersion degree of the fillers can be significantly enhanced at a golden mixing ratio so that a pathway for electric conduction is effectively formed.…”
Section: Resultsmentioning
confidence: 62%
“…The synergistic role of CNTs in improving the electrical conductivity of LDPE/GNP composites prepared by melt mixing was also observed in Haznedar's study [17]. At present, a large number of studies of polymer/carbon nanofiller composites have been reported, however much fewer reports have been published on the comparison of the reinforcement effect of carbon nanofillers with different dimensions [14,18,19] and polymer composites filled with hybrid carbon nanofillers [16,17,20].…”
Section: Introductionmentioning
confidence: 57%
“…In order to achieve lower cost or a better balance of properties, the incorporation of hybrid carbon nanofillers with different dimensions is a possibility in preparing multifunctional polymer composites. Kim et al [16] found that the HDPE composites filled with 0.5 wt.% GNPs and 2 wt.% CNTs exhibited a low electrical resistivity of 3.1 • 10 2 X • cm, while the unary carbon nanofiller reinforced composites filled with 0.5 wt.% GNPs or 2 wt.% CNTs alone showed a high resistivity. The synergistic role of CNTs in improving the electrical conductivity of LDPE/GNP composites prepared by melt mixing was also observed in Haznedar's study [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that carbon-based nanomaterials have substantial advantages in reinforcing the polymer matrix in terms of mechanical properties, and so on. [26][27][28][29][30] For graphite nanosheets or nanoplatelets, in particular, the super mechanical modulus and high aspect ratio led to a significant increase in the mechanical properties of polymer composites. To inspect the tensile properties of xGnP/PEN films, a 10-cm long and 1-cm wide nanocomposite film with the thickness of 10 mm was chosen for the tensile properties testing.…”
Section: Resultsmentioning
confidence: 99%